Water Balance Assessment, Land Use Land Cover Change and Increasing Water Demand in Three Major Watersheds in Jember, East Java, Indonesia - Indarto Indarto; Entin Hidayah; Erwan Bagus Setiawan (Department of Geography Education, University of Jember, 2023)
Jember Regency is the third largest agricultural area in East Java Province. Expansion of built-up and agricultural areas occurred and significantly changed the landscape. Moreover, increasing both types of land cover will increase water consumption. Therefore, there may be changes in the condition of the water balance in the Jember Regency area. This area has three major watersheds: Bedadung, Mayang, and Tanggul. This study evaluated the water balance condition at the three major watersheds in Jember, East Java, Indonesia. The WEAP (Water Evaluation and Planning) model calculated the water balance. Research procedures include (1) inventory of spatial and non-spatial data; (2) setup of the WEAP scheme; (3) Calibration; (4) Validation; and (5) Simulation of water balance model in scenario increasing water demand and land-use change). From 1997 to 2020, the water balance was evaluated using a 10-day interval. The results show that from the November 1st to August 2nd periods, the watershed can supply all demand sites with 100% coverage. However, from August 2nd t to October 3rd periods, the watershed’s ability to supply the water needs decreased. This deficit is due mainly to the uneven rainfall distribution between rainy and dry seasons. Variation in annual rainfall received from 1997 to 2020 also affects the water balance’s surplus and deficit. The fluctuation of land-use change contributed to the surplus and shortage of water balance. Keywords : Supply; Demand; Water Balance; WEAP; Jember; East Java Copyright (c) 2023 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License